Analisis Ketersediaan dan Kebutuhan Ruang Terbuka Hijau di Kecamatan Rantepao, Kabupaten Toraja Utara. - Fahirah Agung; Agus Salim; Tru Budiharto (Fakultas Teknik Universitas Bosowa, 2023)
One most of support influential on quality environment and quality of life a community is Green Open Space. But the availability of Green Open Space in Rantapeo District has not reached the standard 30% of the total area. While the population growth and urban development are increasing drastically will hinder various city service efforts, and at the same time also have a negative impact on nature protection. The purpose of this study aims to analyze needs of Green Open Space and identify strategies for providing Green Open Space, this study uses a qualitative approach and a quantitative. Use analysis is analysis needs Green Open Space and uses an analysis tool (SWOT) to produce strategies and synchronizes them with applicable regulations using a qualitative approach related to the problem causes of low availability of Green Open Space.